Changes in meaning and function studies in historical linguistics with a focus on Spanish - Fernández Jaén, Jorge; Provencio Garrigós, Herminia (IVITRA research in linguistics and literature ;, 2020)
"Diachronic linguistics has been experiencing a strong revival during the last few decades, since an increasing number of researchers have assumed that evolutionary and historical factors must be considered to properly understand how natural languages work. This book offers new data and insights on some of the research lines which are currently being developed within the framework of diachronic language research. The papers brought together in this volume are characterized both by their originality and by their methodological diversity; the reader will thus find herein theoretical as well as empirical works, undertaken from various perspectives of analysis (diachronic cognitive semantics, grammaticalization theory, discursive traditions, historical phraseology, etc.). The final outcome is an eclectic volume which offers valuable information for every reader, regardless of whether they are experienced linguists or junior researchers willing to know the latest epistemological advances in this discipline"--